Compatible Pair Of Nontrivial Action For Finite Cyclic 2-Groups - Sahimel Azwal, Sulaiman; Mohd Sham, Mohamad; Yuhani, Yusof; Shahoodh, Mohammed Khalid (Universiti Malaysia Pahang, 2016)
The nonabelian tensor product for a pair of groups is defined when the action act compatibly on each other. By using the necessary and sufficient conditions of two finite cyclic 2-groups, the compatible pairs of nontrivial actions for two same finite cyclic 2-groups with same order of actions are determined. Then, the general exact number of compatible pairs of nontrivial actions for two same finite cyclic 2-groups with same order of actions is given.